Combination immunotherapy strategies in advanced non-small cell lung cancer (NSCLC): Does biological rationale meet clinical needs?. (November 2017) - Attili, Ilaria; Passaro, Antonio; Pavan, Alberto; Conte, PierFranco; De Marinis, Filippo; Bonanno, Laura
Highlights: Molecular background for combination immunotherapy in NSCLC. Activity of combination strategies including immune checkpoint inhibitors in NSCLC. Main safety issue for combination strategies. Abstract: Immune checkpoint inhibitors (ICIs) have emerged as one of the main new therapeutic options for advanced non-small cell lung cancer (NSCLC) patients. Even though they demonstrated superiority towards standard chemotherapy in different disease settings, the response rates do not exceed 45% in highly molecularly selected patients. This is related to known limitations of the available biomarkers, as well to the complex and dynamic nature of tumor microenvironment. The study of the different strategies adopted by tumor cells to escape the immune system lays the basis of the new combination strategies. This review focuses on analyzing the biological rationale and early clinical data available concerning therapeutic strategies combining ICIs together, ICIs with different regimens and schedules of standard chemotherapy, ICIs with tyrosine kinase inhibitors, ICIs with antiangiogenic agents and ICs with radiotherapy.